Effect of pomiferin administration on kidney ischaemia-reperfusion injury in rats - Bartošíková, Lenka; Nečas, Jiří; Bartošík, Tomáš; Pavlík, Martin; Fráňa, Petr (Interdisciplinary toxicology, 2010)
The aim of the study was to analyse protective effects of different doses of pomiferin in therapy of reperfusion injury. Rats were randomly divided into five groups (n=10). One group was intact. Three medicated groups and one placebo group were subjected to ischaemia and reperfusion of the left kidney. Pomiferin was administrated by single gastric gavage in 2 ml of 0.5% Avicel solution in doses of 5, 10 and 20 mg/kg. The placebo group was given only Avicel solution. On day 15, all the animals were exsanguinated and the reperfused kidneys were recovered. Selected biochemical markers were assessed in blood: antioxidative enzymes, total antioxidative capacity, malondialdehyde, creatinine, urea and uric acid. Creatinine, urea and total proteins were analysed in urine and 24-hour diuresis was recorded. The kidney tissue samples were used for histopathological examination.The results confirmed the expected protective effects of pomiferin. Pomiferin supported defensive reactions of the body against free radicals (increased levels of superoxide dismutase, total antioxidative capacity), decreased lipid peroxidation (decreased malondialdehyde) and contributed to the recovery of kidney functions (creatinine and urea in blood). The best biochemical and histopathological results were achieved after pomiferin administration in the dose of 5 mg/kg.
Keywords: antioxidative effect; ischaemia-reperfusion; pomiferin; kidney; therapy